Effects of strain and electric field on electronic structures and Schottky barrier in graphene and SnS hybrid heterostructures. (November 2016) - Xiong, Wenqi; Xia, Congxin; Zhao, Xu; Wang, Tianxing; Jia, Yu
Abstract: The structural stability and electronic properties of monolayer and bilayer graphene with SnS hybrid heterostructures are studied by using the first-principle methods. The intrinsic electronic properties of SnS and graphene are preserved, and p -type Schottky contacts with the significantly small barrier height are formed in the van der Waals (vdW) heterostructures. In the graphene/SnS (G/S) heterostructure, the p -type Schottky contacts can be changed to Ohmic contacts by decreasing the interlayer distance, and it is also turned to n -type Schottky contacts by applying external electric field. However, the Schottky barrier of graphene/SnS/graphene (G/S/G) heterostructure is insensitive to the external electric field. Moreover, in the SnS/graphene/graphene (S/G/G) heterostructure, the external electric field can easily induce the transition from p -type to n -type Schottky contacts, then to Ohmic contacts. These studies provide a promising route to design new graphene-based vdW heterostructures and explore its potential applications in electronic and optoelectronic devices.